The preparation of optical isomers in the camphor series, and investigation of their melting point curves - Somerville, Ian Campbell (The University of Edinburgh, 1926)
INTRODUCTORY • PREPARATION of OPTICAL ISOMERS • DETERMINATION of CURVES • DISCUSSION of RESULTS